2020
DOI: 10.2337/dc19-2367
|View full text |Cite
|
Sign up to set email alerts
|

Both Prediabetes and Type 2 Diabetes Are Associated With Lower Heart Rate Variability: The Maastricht Study

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 32 publications
6
42
0
2
Order By: Relevance
“…Interestingly, although Pre-DM individuals present modestly raised glucose levels, similar cardiac abnormalities of DM subjects were also observed in these patients. For example, Coopmans et al has reported that Pre-DM and DM are similarly associated with reduction of heart rate variability [17]. Previous studies including ours have also indicated that patients with DM or Pre-DM have similar pro-atherogenic lipid profiles [12].…”
Section: Introductionsupporting
confidence: 56%
“…Interestingly, although Pre-DM individuals present modestly raised glucose levels, similar cardiac abnormalities of DM subjects were also observed in these patients. For example, Coopmans et al has reported that Pre-DM and DM are similarly associated with reduction of heart rate variability [17]. Previous studies including ours have also indicated that patients with DM or Pre-DM have similar pro-atherogenic lipid profiles [12].…”
Section: Introductionsupporting
confidence: 56%
“…This may mean that transcatheter closure could reduce the risk of cardiac death in patients with ASD and improve prognosis. Moreover, patients with diabetes or prediabetes have lower HRV [25,26]. Diabetes-related cardiac autonomic dysfunction plays an important role in the decrease in HRV [27].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have concerned the association between autonomic disfunction and prediabetes [ 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] ( Table 3 ). A great diversity of results was observed in these studies when it comes to the discussed glucose metabolism disorders, the size of the groups undergoing research, and cardiovascular autonomic neuropathy (CAN) testing methods.…”
Section: Methodsmentioning
confidence: 99%
“…Nine studies followed IGT defined according to the WHO 1999 guidelines with 2-h post-load glucose levels between 140 and 199 mg/dL (7.8–11.0 mmol/L) in OGTT [ 78 , 81 , 84 , 85 , 86 , 87 , 88 , 89 ]. One study took into consideration an IFG-IGT group (defined according to ADA 2003 and WHO 1999 guidelines) [ 87 ], while two studies did not differentiate between these prediabetic states [ 90 , 91 ]. Seven studies included a small group (below 200 participants) [ 76 , 77 , 81 , 84 , 86 , 88 , 90 ], and six studies encompassed more than 1000 participants [ 76 , 79 , 80 , 82 , 83 , 91 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation